2023
DOI: 10.1186/s12950-023-00333-2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular features of COVID-19 associated ARDS: therapeutic relevance

Abstract: The severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection can be asymptomatic or cause a disease (COVID-19) characterized by different levels of severity. The main cause of severe COVID-19 and death is represented by acute (or acute on chronic) respiratory failure and acute respiratory distress syndrome (ARDS), often requiring hospital admission and ventilator support.The molecular pathogenesis of COVID-19-related ARDS (by now termed c-ARDS) is still poorly understood. In this review we will d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 237 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that in COVID-19 related ARDS, there is a tendency toward a more severe phenotype related to extended pulmonary endothelial injury in the early phase of the disease [ 37 ]. Nevertheless, Ang-2 and ICAM-1 were the only markers observed to be elevated in non-survivors in contrast to survivors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in COVID-19 related ARDS, there is a tendency toward a more severe phenotype related to extended pulmonary endothelial injury in the early phase of the disease [ 37 ]. Nevertheless, Ang-2 and ICAM-1 were the only markers observed to be elevated in non-survivors in contrast to survivors [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A dysregulated inflammatory response is also a hallmark alteration in severe COVID-19 cases, especially when causing ARDS [71][72][73]. IL-6 elevation in plasma has been extensively studied in C-ARDS, showing a direct correlation with disease severity [71].…”
Section: Biomarkers In Covid Ards and Non-covid Ardsmentioning
confidence: 99%
“…Understanding the cellular and molecular mechanism that is the underlying cause of the development of ARDS in COVID-19 infected patients is important. This will give insights into the development of well-efficient therapies for this disease [22] .…”
Section: Introductionmentioning
confidence: 99%